Geomorphology and (palaeo-)hydrography of the Southern Atbai plain and western Eritrean Highlands (Eastern Sudan/Western Eritrea). Issue 2 (1st December 2021) - Costanzo, Stefano; Zerboni, Andrea; Cremaschi, Mauro; Manzo, Andrea
ABSTRACT: We present the geomorphology of the Southern Atbai Plain (Eastern Sudan) and the western edge of the Eritrean Highlands (Western Eritrea), in the eastern Sahel. The mountainous area consists of Paleo-Proterozoic gneiss and Neo-Proterozoic igneous rocks and meta-volcanic assemblages shaped as inselbergs and whaleback landforms by weathering. Bare-rock hills emerge from a gentle glacis that oversees the Southern Atbai alluvial plain, located between the Atbara and Gash Rivers. The plain features the SSE-NNW-oriented endorheic terminal fan of the Gash River and is crossed by intricate Early to Late Pleistocene paleochannels, whose evolution was controlled by the interplay between Quaternary regional tectonics and arid to humid climatic and environmental oscillations. The map is intended to interpret the evolution of local landscape, thus representing a tool for reconstructing the spatial and temporal distribution of Late Quaternary archaeological features and their functional relationships with the fossil fluvial system and the western foothills.